2019
DOI: 10.1002/nau.24149
|View full text |Cite
|
Sign up to set email alerts
|

The aging bladder phenotype is not the direct consequence of bladder aging

Abstract: Aims The prevalence of urinary dysfunction increases with age, yet therapies are often suboptimal. Incomplete understanding of the linkages between system, organ, and tissue domains across lifespan remains a knowledge gap. If tissue‐level changes drive the aging bladder phenotype, parallel changes should be observed across these domains. In contrast, a lack of inter‐domain correlation across age groups would support the hypothesis that urinary performance is a measure of the physiologic reserve, dependent on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Active and passive properties of mouse bladder wall preparations. Intact detrusor strips from aged mice were less contractile to EFS or carbachol stimulation in agreement with some studies, 19 but at variance with others that reported either no change, 20 or even enhanced contractile function. 21 There was also no evidence for functional detrusor denervation in aged mice as the decline of EFS and agonist-induced responses in aged mice were similar (T carb /T max,EFS similar, Table 1), and the extent of atropine resistance was also the same.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Active and passive properties of mouse bladder wall preparations. Intact detrusor strips from aged mice were less contractile to EFS or carbachol stimulation in agreement with some studies, 19 but at variance with others that reported either no change, 20 or even enhanced contractile function. 21 There was also no evidence for functional detrusor denervation in aged mice as the decline of EFS and agonist-induced responses in aged mice were similar (T carb /T max,EFS similar, Table 1), and the extent of atropine resistance was also the same.…”
Section: Discussionsupporting
confidence: 90%
“…The overall implication is that data from aged animals does not represent a homogeneous group and that comorbid conditions may overwhelm any effect of age per se, 20 and if translated to elderly humans would underlie their variable incidence of urinary urgency. One direct hypothesis that may be tested is that when ATP release is much greater in some aged animals or humans, so also should afferent activity as a pathophysiological basis of increased urgency.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the effect of aging on urodynamic parameters has been assessed among women with stress urinary incontinence (SUI) with a mean age of 57 years [14]. They found that Qmax, voided volume and Pdet@Qmax decreased and PVR and desire to void increased significantly with age after 60 years [10]. We also found a weak negative correlation between Pdet and age.…”
Section: Discussionmentioning
confidence: 70%
“…The cause of urethral dysfunction is hypothesized as decreased synthesis of NO, a molecule that relaxes urethral smooth muscle [21], and increased synthesis of the endogenous inhibitor of NO-synthase, with age [22]. Another recent animal study showed that the consistency of layer thickness and nuclear density of the bladder wall structure in mice is preserved following maturation, but this may differ in humans [10]. A correlation between urethral pressure and estrogen levels during the menstrual cycle is expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation